Kriminalisasi Terhadap Pekerja Seks Komersial Melalui Online dalam Pembaharuan Hukum Pidana - I Gede Yoga Pratama; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Prostitution is behavior that is openly subject to adultery without any marriage bond. Nowadays prostitution is easy to find on various social media. Commercial-related regulations have been regulated in the Criminal Code, Law no. 19 of 2016 concerning Information and Electronic Transactions, Law no. 44 of 2008 concerning Pornography, Law no. 21 of 2007 concerning the Crime of Human Trafficking. This study aimed to examine the criminal law regulation of online sex workers according to positive law and uncover criminal sanctions against online sex workers in the future. This study was designed using normative legal research, with a Legislative approach. The legal materials used were primary legal materials and secondary legal materials. Data were collected using documentation study techniques and literature studies, then analyzed using systematic interpretation techniques. The results of the study indicated that sanctions for pimps are regulated in the Criminal Code, Law no. 21/2007, Law no. 44/2008, and Law no. 19/2016, and only article 284 of the Criminal Code concerning adultery that can ensnare prostitutes and customers if they have a family, and criminal sanctions for commercial sex workers in the future are contained in articles 425 to 428 of the Draft Criminal Code.